Bifocal pacing - A novel cardiac resynchronization therapy? Results of bifocal pacing study and review of the current literature - Bulava, Alan; Lukl, Jan (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2006)
Background: Bifocal pacing (BFP) has been proposed as a more feasible alternative of cardiac resynchronization therapy (CRT). AIM: To evaluate BFP in patients with severe congestive heart failure and significant intraventricular conduction delay and to compare it with biventricular pacing (BVP). METHODS: Both echocardiographic examination including tissue Doppler imaging and invasive measurements of cardiac hemodynamics was performed under basal conditions and during BFP and BVP. RESULTS: 50 patients were included: 29 patients with ischemic heart disease (IHD), 21 patients with idiopathic dilated cardiomyopathy (IDCM). Left ventricular (LV) pressure gradient (dp/dt max) increased during BFP compared to the baseline (13.4 %, 95 % CI 9.2-17.6 %, p < 0.0001) and a further increase was achieved during BVP (29.5 %, 95 % CI 23.7-35.4 %, p < 0.0001). A significant correlation was found between the distance of the right ventricular apical and outflow tract leads and percentage of dp/dt max increase in IDCM patients (r = 0.72, p < 0.001), but not in IHD patients. Interventricular mechanical delay (IVMD) decreased in BFP compared to baseline (43 +/- 22 ms vs. 53 +/- 31 ms, p = 0.006). BVP produced even shorter IVMD (22 +/- 19 ms, p < 0.0001). In all patients, the regional systolic contraction times were significantly shortened, corresponding with prolongation of the respective regional diastolic filling times during both BFP (p < 0.05 for all segments) and BVP (p < 0.001 for all segments). The effect of BVP on regional systole shortening was more pronounced. CONCLUSIONS: BFP improves LV hemodynamics by decreasing the inter- and intraventricular conduction delays. The leads in the right ventricle should be placed at the longest achievable distance. BVP is superior to BFP.
Keywords: Aged; Ventricular Function, Left; Aged, 80 and over; elektrokardiografie; Heart Failure; kardiostimulace umělá; Hemodynamics; Arrhythmias, Cardiac; lidé; lidé středního věku; senioři; ženské pohlaví; Female; mužské pohlaví; hemodynamika; Cardiac Pacing, Artificial; Middle Aged; senioři nad 80 let; Humans; Male; srdeční selhání; srdeční arytmie; funkce levé komory srdeční; Electrocardiography